Upaya Meningkatkan Motivasi Belajar Siswa melalui Media Digital Canva dalam Pembuatan Video Pembelajaran Ibadah Praktis pada Mata Pelajaran Fiqih di MTs Darul Ulum Budi Agung - Sinta, Rahma; Fanreza, Robie (EduInovasi: Journal of Basic Educational Studies, 2024)
Modern education today may be very different from education in the past. Nowadays, education is more constructive and heavily relies on information and communication technology. Learning should be able to develop skills such as critical thinking and problem solving, creativity and innovation, communication, collaboration. Therefore, teachers must be creative and innovative educators in creating learning media that can enhance students' motivation to learn, one of which is in selecting varied and digital-based learning media in accordance with technological developments in the current era. The method used in this research is the qualitative experimental method using an experimental approach. The aim of this research is to describe creative and innovative learning media by utilizing Canva digital media to create learning media in the form of videos in the subject of Fiqih. The first results of this research is the increase in students' learning motivation marked by the increasing interest of students in observing the learning with the created media, and the improvement in students' discipline, second, the features available in the digital media Canva make it easier for teachers and students to create learning media, third, because there are not many teachers or students who are familiar with digital media Canva, further research is needed to achieve even better results.